Israel and the rise of the neoconservatives, 1960-1976 - Hummel, Daniel G., author; Citino, Nathan J., advisor; Lindsay, James E., 1957-, advisor; Yasar, Gamze, committee member (Colorado State University. Libraries, 2010)
Despite the importance of neoconservatism in modern American history, inadequate attention has been paid to how the neoconservatives developed their fixation with the state of Israel. The link between the two has either been explained as a natural extension of ethnic loyalty or as part of a conspiratorial plot by un-American, separately Jewish interests. This study complicates the common explanations for the neoconservative fixation with Israel by examining the neoconservatives at their temporal roots in the 1960s and 1970s. Particular attention is given to the context in which neoconservatives coalesced and rallied around Israel as a central component of their new ideology. By reexamining the rise of the neoconservatives in American politics through the lens of their symbolic relationship with Israel, three actors rise as most prominent in their influence on neoconservative thought. On the sub national level Black Nationalists clashed with neoconservatives in the context of 1960s domestic upheaval. On the national level, Kissinger's détente policies were perceived by neoconservatives as posing an existential threat to Israel's survival. Finally, on the international level, Third World denunciations of Israel provided neoconservatives with a stage to present their vision of Israel to the American public. Examining these conflicts substantiates the widely recognized neoconservative fixation with Israel with historical context. This study relies on the writings of prominent neoconservatives, including Norman Podhoretz, Nathan Glazer, and Daniel Patrick Moynihan, the periodical journal Commentary, and a wide variety of other primary sources that address neoconservative actions and motivations from 1960-1976.
Department Head: Diane Claire Margolf.